การพัฒนาเครื่องฝึกการทรงตัวโดยใช้เกมส์คอมพิวเตอร์สำหรับผู้สูงวัยและผู้ป่วยที่มีความผิดปกติในการทรงตัว - มานะ ศรีวิรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This thesis presents the development of a computerized game-based balance machine for elderly and patients with balance problems. The developed system consists of 4 main parts; 1) force platform, 2) a processing box, 3) a support rail and 4) software. The force platform are installed with four polymer based force sensors. The four sensors are used to sense the location of the center of gravity (COG) of a test object. The developed platform can measure a static load up to 174 kg. The processing box converts sensor resistances into voltage signals as well as performs A/D conversion with an 8-bit resolution. The digitized data will be sent to a computer via serial communication with a sampling frequency of 20 Hz. The developed software are a program for determining the COG location and a game-based balance training program. The developed system can indicate the COG location in xand y-axis with accuracy of +-4.1% and 7.8%FSO, respectively. Area sway of 37 healthy people with the aged between 40-60 years have been measured. The average values of area sway for male and female are 0.820.49 cm[superscript 2] and 1.12+-0.79 cm2, respectively. A game-based balance training program has been developed and tested with 2 elderly and 2 patients with balance problems. All participants have been trained with this game-based program, 30 minutes a day for 10 days. The balance assessment have been performed before and after training using timed single leg stance with eye open, timed up and go test and Berg balance scale. All participants have the improvement in the balance ability after the training program